2019
DOI: 10.1177/1071181319631083
|View full text |Cite
|
Sign up to set email alerts
|

Improved Accuracy Test Method for Mobile Eye Tracking in Usability Scenarios

Abstract: Eye tracking has been used in usability testing for many years to gain objective measurements to inform label, instruction, and product design. With many different testing environments, possible participants, hardware, and software, key metrics can vary greatly. These metrics can also vary for different studies, so a standardized test method, metrics, and calculation method are proposed in this study. The Tobii Pro Glasses 2 is a mobile eye tracker that does not significantly affect user mobility compared to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Low gaze capture may result from incorrect calibration vs. actual distance to the stimuli (MacInnes et al, 2018 ), incorrect positioning of the eye-tracking glasses (i.e., resulting in the front-view camera being directed away from the AOIs) or inherent inaccuracy (e.g. participants with deficient visual acuity, uncontrolled head movement) (Thibeault et al, 2019 ). We screened participants for sufficient visual acuity and performed individual calibration for each subject in the actual testing room, following the manufacturer’s instructions which involve a one-point calibration method with a card placed at comparable distance to the actual stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low gaze capture may result from incorrect calibration vs. actual distance to the stimuli (MacInnes et al, 2018 ), incorrect positioning of the eye-tracking glasses (i.e., resulting in the front-view camera being directed away from the AOIs) or inherent inaccuracy (e.g. participants with deficient visual acuity, uncontrolled head movement) (Thibeault et al, 2019 ). We screened participants for sufficient visual acuity and performed individual calibration for each subject in the actual testing room, following the manufacturer’s instructions which involve a one-point calibration method with a card placed at comparable distance to the actual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 73% of recordings provided 80% or more of gaze capture. Based on the sample size ( n = 149 recordings) we believe this limitation is acceptable, however, pre-test point-to-point and trial-to-trial variability checks would probably improve accuracy and are recommended (Thibeault et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from establishing the origin of the gaze vector (e.g., eye position), expressing point of gaze with a world-based frame of reference can be affected by the accuracy and precision of the eye tracking system ( Ooms, 2015 ). Multiple factors influence gaze calibration and data quality, including task factors such as viewing distance defined as the distance between a participant and the location being fixated (such as Figure 1 ‘C’) and viewing angle defined as the angle between gaze origin and the location being fixated (such as Figure 1 ‘ a ’) ( Blignaut & Wium, 2014 ; Thibeault et al, 2019 ). Parallax error represents a common limitation associated with viewing distance and head-mounted eye-trackers, which occurs when the distance between the point of regard and the user (viewing distance) is different to when the system was calibrated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the combined influence of viewing distance and visual angle outlined above are simple to translate into world-space values using trigonometry, the accuracy of eye-tracking systems (in terms of visual angle) has also been shown to be influenced by a range of participant factors such as eye color, contact lens use, and eye lash length (e.g., Blignaut & Wium, 2014 ; Thibeault, et al, 2019 ). Furthermore, MacInnes et al (2018) also reported that accuracy decreased as viewing distance increased.…”
Section: Introductionmentioning
confidence: 99%